ANCAMAN TERHADAP KEANEKARAGAMAN HAYATI KALIMANTAN: IMPLEMENTASI NILAI PERSATUAN DAN KEADILAN EKOLOGIS - Imroatul Azizah; Lailatul Fadillah Kamal; Zanetha; Suryaningsih (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
Kalimantan is renowned for its exceptionally high biodiversity, making it one of Indonesia’s most ecologically significant regions. However, this rich natural environment faces serious threats from human activities such as deforestation, plantation expansion, mining, and land conversion. These actions not only endanger endemic species but also disrupt ecological balance and negatively affect the livelihoods and welfare of local communities who depend on natural resources for their daily needs. This study employs a qualitative-descriptive approach based on literature review to examine these environmental threats and to analyze how Pancasila values particularly principles 3 (unity), 4 (deliberation), and 5 (social justice) can guide conservation efforts. Findings indicate that short-term economic exploitation often neglects ecological concerns and exacerbates social inequalities. The principle of unity is crucial for reconciling the sometimes conflicting interests of government, private sectors, and local communities. Deliberation ensures that conservation policies are developed inclusively, while social justice protects the rights and welfare of local residents, particularly indigenous and marginalized groups. Moreover, the concept of ecological justice emphasizes the responsibility of the current generation to safeguard environmental resources for future generations. Effective conservation in Kalimantan, therefore, requires adherence to Pancasila values and collaborative efforts across sectors, combining ecological preservation with social equity. Such an approach promotes sustainable development that balances human needs with the protection of biodiversity and ecosystem integrity.